Analisis ketahanan hidup pasien pneumonia dengan model regresi cox di RSUD Aceh Tamiang tahun 2022 - Rima, Fitriah Putri; Santosa, Heru; Arde, Lanova Dwi; Lubis, Ismil Khairi (TROPHICO: Tropical Public Health J., 2024)
Globally, pneumonia is the fourth leading cause of death in the world and the deadliest infectious disease. The 2019 Global Burden of Disease (GDB) study stated that lower respiratory tract infections were responsible for more than 2.49 million deaths with the highest mortality rate in patients over 70 years of age at 1.23 million and 672,000 deaths in patients less than 5 years old. With an increase in cases and high mortality rates in pneumonia, it is necessary to analyze the survival of pneumonia patients by conducting a survival analysis. The design of this study was a retrospective cohort study that observed pneumonia patients who had been hospitalized by looking for factors associated with pneumonia mortality. The population in this study was 1,371 with a sample size of 363 patients. The results of the research factor of vitamin C p-value (0.173) > (0.05) there is no relationship of vitamin C. The factor of ventilator p-value (0.001) < (0.05), there is a relationship between ventilator and pneumonia survival with HR = 1451.802. The factor of decreased consciousness p-value (<0.0001) < (0.05) there is a relationship between decreased consciousness and pneumonia survival with HR = 3.923. The severity factor p-value (0.011) < Î± (0.05), there is an association of severity with the survival of pneumonia with HR = 3739.9. The author suggests that medical personnel prioritize patients using ventilators and their severity to prevent death and provide optimal care on day 12 because it has a high failure rate. Keywords: Survival. Pneumonia, Cox regression